Sovereignty as symbolic form - Bartelson, Jens (Abingdon, Oxon : Routledge, 2014)
'This book is a critical inquiry into the meaning and function of sovereignty in the present and argues that the meaning and functions performed by this concept have changed significantly during the past decades, with profound implications for the ontological status of the state and the modus operandi of the international system as a whole. Although we have grown accustomed to regard sovereignty both as a defining characteristic of the modern state and a constitutive principle of the international system, this book argues that recent changes indicate that sovereignty has been turned into a grant contingent upon its responsible exercise in accordance with the norms and values of an imagined international community. This book has grown out the dissatisfaction with the author's previous work on sovereignty and the state, and argues that a new concept of sovereignty is needed today in order to clarify the logic of its current usage in theory and practice alike and its connection to broader concerns of social ontology: what kind of world do we inhabit, and of what kind of entities is this world composed? This book will be of interest to students of International Relations, Critical Security and International Politics'--
Includes bibliographical references and index.
Keywords: Sovereignty; International relations